2002
DOI: 10.1021/jm0110340
|View full text |Cite
|
Sign up to set email alerts
|

Novel Selective PDE4 Inhibitors. 3. In Vivo Antiinflammatory Activity of a New Series of N-Substituted cis-Tetra- and cis-Hexahydrophthalazinones

Abstract: The synthesis and biological activities of a series of N-substituted cis-4a,5,6,7,8,8a-hexa- and cis-4a,5,8,8a-tetrahydro-2H-phthalazin-1-ones are described. It was found that compounds bearing a cycloalkyl group at the 2-position exhibit the highest PDE4 inhibitory activities (pIC(50) = 8.6-9.4). The N-cycloheptyl- and N-adamantanyltetrahydrophthalazinones (7h, 8, 10, 11) show high in vivo antiinflammatory activities after oral application. Additionally, some phthalazinones were found to exhibit potent suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The synthesis schemes 1 and 2 depict the synthetic routes of all compounds, some of which (1, 4, 5, 9, 11 and 14-18) have been published before as PDE4 inhibitors. 18,22 , while the others (6,7,8,10,12,13,(19)(20)(21)(22)(23)(24)(25) are new. For the compounds with the 3,4-dimethoxy (4, 5, 8-11) and the 4methoxy (6) substitution the synthesis route (Scheme 1) started with a Friedel-Craft acylation.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis schemes 1 and 2 depict the synthetic routes of all compounds, some of which (1, 4, 5, 9, 11 and 14-18) have been published before as PDE4 inhibitors. 18,22 , while the others (6,7,8,10,12,13,(19)(20)(21)(22)(23)(24)(25) are new. For the compounds with the 3,4-dimethoxy (4, 5, 8-11) and the 4methoxy (6) substitution the synthesis route (Scheme 1) started with a Friedel-Craft acylation.…”
Section: Synthesismentioning
confidence: 99%
“…Subsequent condensation with hydrazine gave the pyridazinones which could be alkylated using sodium hydride in DMF. In all other cases (1,7,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) the route started with a Grignard reaction (Scheme 2) to obtain the gamma-ketopropionic acids. These carboxylic acids were then converted to the corresponding pyridazinones using the same chemistry as already outlined in scheme 1.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Hexahydrophthalazinones family appears as a potent family of PDE4 inhibitors. 89 The structure-activity relationship studies showed that compounds bearing a cycloalkyl group at the position 2 exhibit the highest PDE4 inhibitory activities [p(IC 50 ) ¼ 8. 6-9.4].…”
Section: Miscellaneousmentioning
confidence: 99%
“…Several triazolophthalazines were found to exhibit antifungal and antibacterial activities 1–3. In addition, phthalazines and triazolophthalazines were found to exhibit anti‐inflammatory profiles 4–7. Among the already marketed COX‐2 inhibitors that comprise pyrazole nucleus, celecoxib (4‐[5‐(4‐tolyl)‐3‐(trifluoromethyl)‐1 H ‐pyrazol‐1‐yl]benzenesulfonamide), occupies a unique position as a potent and GI‐safe anti‐inflammatory and analgesic agent.…”
Section: Introductionmentioning
confidence: 99%